2017
DOI: 10.1016/j.prevetmed.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Johne’s disease in the eyes of Irish cattle farmers: A qualitative narrative research approach to understanding implications for disease management

Abstract: Bovine Johne's Disease (JD) is a disease characterised by chronic granulomatous enteritis which manifests clinically as a protein-losing enteropathy causing diarrhoea, hypoproteinaemia, emaciation and, eventually death. Some research exists to suggest that the aetiologic pathogen Mycobacterium avium subspecies paratuberculosis may pose a zoonotic risk. Nationally coordinated control programmes have been introduced in many of the major milk producing countries across the world. However, JD is challenging to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 24 publications
2
39
0
Order By: Relevance
“…Many current studies on farmer behavior rely on questionnaire survey asking self-reported practice; however, this type of study needs a careful consideration because the discrepancy between self-reported and actual behavior has been repeatedly identified ( 106 108 ). It may be the time to employ a more rigorous qualitative method such as biographical narrative interpretive method ( 29 , 109 )—a method to acquire interviewee's real-life experience—and quantitative studies using objective measures of farmers' behaviors ( 67 , 110 , 111 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many current studies on farmer behavior rely on questionnaire survey asking self-reported practice; however, this type of study needs a careful consideration because the discrepancy between self-reported and actual behavior has been repeatedly identified ( 106 108 ). It may be the time to employ a more rigorous qualitative method such as biographical narrative interpretive method ( 29 , 109 )—a method to acquire interviewee's real-life experience—and quantitative studies using objective measures of farmers' behaviors ( 67 , 110 , 111 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Garforth et al reported that UK sheep farmers often demonstrated that they were willing to vaccinate animals against bluetongue once they heard the disease occurred in their region ( 28 ). Another qualitative study on Johne's disease suggested that farmers may not invest resources into controlling disease until they see clear evidence of disease on their farms ( 29 ). This “wait and see” attitude of farmers toward implementing on-farm biosecurity practices has been repeatedly reported in literature.…”
Section: Disease-related Factors Relevant To Farmers' Dynamic Behaviomentioning
confidence: 99%
See 1 more Smart Citation
“…Although financial considerations are important for some farmers, personal values and belief systems also influence their behaviour [25]. The perceived level of disease in a country and a farmer's experience of controlling other diseases impacts farmers' views about the importance of control programmes, and thus the likelihood of success [26].…”
Section: Drivers For Producer Engagement In Control Programmesmentioning
confidence: 99%
“…Under this framing, various practices associated with livestock trading have been previously studied including maintaining a closed herd (12, 13), verifying the disease status of purchased animals (1416), and considering the disease risk status of source farms and regions (10, 17). Other studies suggested that farmers perceive these practices as being effective, but often impractical (18), which may partially explain why farmers do not often implement these measures. These studies often use behavioralist approaches that focus on the motives, values, and attitudes that determine farmers' decisions.…”
Section: Introductionmentioning
confidence: 99%